2020
DOI: 10.1080/17512433.2020.1814141
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a putative protection against myocardial injury in COVID-19 infection

Abstract: The coronavirus disease 2019 (COVID-19) reached pandemic proportions in March 2020 with unexpectedly rapid spread and serious health and social impacts. In the middle of August, the population of infected patients worldwide has risen to more than 20 million with 750 000 deaths. Number of severely affected patients in some countries overwhelms the capacities of hospitals and places insurmountable demands on healthcare systems. Acute respiratory distress syndrome (ARDS), as the most frequent serious complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Finally, last year, under the direction of Professor Reuter, authors published several articles claiming that MEL could effectively treat the new COVID-19 infection [74][75][76][77][78]. Moreover, the authors suggested that MEL may be useful in the fight against COVID-19-induced disorders of various organs e.g., heart [74,76] and lungs. These assumptions certainly need confirmation and expand the possibilities of further use of MEL in medicine and pharmacology.…”
Section: The Role Of Melatonin In Pathologiesmentioning
confidence: 99%
“…Finally, last year, under the direction of Professor Reuter, authors published several articles claiming that MEL could effectively treat the new COVID-19 infection [74][75][76][77][78]. Moreover, the authors suggested that MEL may be useful in the fight against COVID-19-induced disorders of various organs e.g., heart [74,76] and lungs. These assumptions certainly need confirmation and expand the possibilities of further use of MEL in medicine and pharmacology.…”
Section: The Role Of Melatonin In Pathologiesmentioning
confidence: 99%
“…The outbreak of the COVID-19 pandemic has not only afflicted everyday life at manifold levels but also introduced novel therapeutic challenges [5,6]. Unfortunately, a number of clinical trials testing antiviral, anti-inflammatory and immunomodulatory substances have brought more disappointment than delight.…”
Section: Sars-cov-2 Ang II Ang 1-7 Interactionmentioning
confidence: 99%
“…Treatment of the hormone significantly healed myocardial injuries, by repressing inflammation (31). Other possible mechanisms of melatonin include the regulation of the rate of autophagy and apoptosis inhibition in mice with CVB3-induced myocarditis (15,31,32).…”
Section: Suggested Mechanisms Of Action Of Melatonin Against Viral Infectionsmentioning
confidence: 99%